Improvement in biohythane production using organic solid waste and distillery effluent. (August 2017) - Mishra, Preeti; Balachandar, G.; Das, Debabrata
Graphical abstract: Highlights: Suitability of organic solid wastes and distillery effluent (DE) for biohythane production. Groundnut deoiled cake and distiller's dried grain with solubles showed 2.73 and 2.61-fold increase in H2 production. 97.7% cost reduction due to the replacement of tryptone with solid wastes. Maximum gaseous energy recovery was 23.93 kcal/L using DE with GDOC. Abstract: Biohythane is a two-stage anaerobic fermentation process consisting of biohydrogen production followed by biomethanation. This serves as an environment friendly and economically sustainable approach for the improved valorization of organic wastes. The characteristics of organic wastes depend on their respective sources. The choice of an appropriate combination of complementary organic wastes can vastly improve the bioenergy generation besides achieving the significant cost reduction. The present study assess the suitability and economic viability of using the groundnut deoiled cake (GDOC), mustard deoiled cake (MDOC), distillers' dried grain with solubles (DDGS) and algal biomass (AB) as a co-substrate for the biohythane process. Results showed that maximum gaseous energy of 23.93, 16.63, 23.44 and 16.21 kcal/L were produced using GDOC, MDOC, DDGS and AB in the two stage biohythane production, respectively. Both GDOC and DDGS were found to be better co-substrates as compared to MDOC and AB. The maximum cumulative hydrogen and methane production of 150 and 64 mmol/L were achieved using GDOC. 98% reduction in substrate input cost (SIC) was achieved using the co-supplementation procedure.